Information and communication technologies for pregnancy care in primary attention level - Ortiz-Chacha, Christian Soledad (Universidad Autónoma de Tamaulipas, 2018)
Maternal care is a priority issue in the provision of health services, this is why we continuously work on improving care for pregnant women. This effort requires basic information that helps establish the effectiveness of the employed strategies, according to the needs of the population. This paper aims to determine the availability, access and use of information and communication technologies (ICT) in the primary care of pregnant women treated by the Health Secretary of the State of Veracruz, Mexico. It also intends to identify the needs that can be resolved or supported through the use of ICT. A questionnaire was designed and administered to a stratified sample of 709 pregnant women who were users of primary care health services in the city of Xalapa. The results showed that 91.9 % of all surveyed women would use at least one of the ICT for their health care during pregnancy. 95.0 % of those interviewed had a mobile phone, of which 68.4 % could connect to the Internet exclusively through cell phones because of the functions that their phones possessed. However, only 58.0 % would use it for their health care. The use of the internet represented a very useful tool to provide administrative, preventive, health promotion or care services. This group expressed interest for the use of ICT for care and attention during their pregnancy, especially to receive health information, detect risks in pregnancy or problems and specific needs of women. These results suggest that it is feasible to promote eHealth and mHealth strategies at the primary care level in Mexico.